2020
DOI: 10.3389/fpsyg.2019.03022
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of the Early Maladaptive Schema in Behavioral Addictions Among Late Adolescents and Young Adults

Abstract: Background: Behavioral addiction (BA) is a recent concept in psychiatry. Few studies have investigated the relationship between BA and early maladaptive schemas (EMSs). EMS is the core of Schema Therapy (ST). According to the ST model, psychiatric disorders result from the development of EMSs in response to unmet emotional needs in childhood. Bach et al. (2018) grouped the 18 EMSs into four domains: (1) disconnection and rejection; (2) impaired autonomy and performance; (3) excessive responsibility and standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 78 publications
0
27
0
2
Order By: Relevance
“…Consequently, they ignored the interrelationships between EMSs. Taken together, these studies [24,25] appear to indicate that EMSs can be important contributors to problematic behaviors associated with general internet use. However, taking into account the differences between subtypes of these problematic online behaviors, such as problematic general internet use, problematic videogame playing, and problematic Facebook use [8,[46][47][48], it is essential to verify EMSs that may be related to the development of these problematic online behavior subtypes.…”
Section: Approval Seekingmentioning
confidence: 79%
See 4 more Smart Citations
“…Consequently, they ignored the interrelationships between EMSs. Taken together, these studies [24,25] appear to indicate that EMSs can be important contributors to problematic behaviors associated with general internet use. However, taking into account the differences between subtypes of these problematic online behaviors, such as problematic general internet use, problematic videogame playing, and problematic Facebook use [8,[46][47][48], it is essential to verify EMSs that may be related to the development of these problematic online behavior subtypes.…”
Section: Approval Seekingmentioning
confidence: 79%
“…Additionally, Aloi et al [24], and Shajari, Sohrabi, and Jomehri [25] demonstrated there is a relationship between problematic internet use and EMSs. More specifically, Aloi et al [24] conducted a study comprising 1075 university students to determine the difference between low and high problematic internet use groups across the EMSs dimensions.…”
Section: Approval Seekingmentioning
confidence: 99%
See 3 more Smart Citations